Parki technologiczne jako narzędzie poprawy konkurencyjności regionu - Kozdęba, Daniel; Budzik, Grzegorz (Technological Parks as the Instrument of Improving the Competitiveness of a Region, 2006)
The article presents selected issues concerning creating and functioning of technology and science and technology parks. There were presented some basic ideas of the conception of functioning of the parks as well as their influence over the stimulation of the enterprise development in the region. Selected problems connected with the process of creating the structure of the park were also taken into consideration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 468-472